2018
DOI: 10.3389/fimmu.2018.01305
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Delta T Cell Therapy for Cancer: It Is Good to be Local

Abstract: Human gamma delta T cells have extraordinary properties including the capacity for tumor cell killing. The major gamma delta T cell subset in human beings is designated Vγ9Vδ2 and is activated by intermediates of isoprenoid biosynthesis or aminobisphosphonate inhibitors of farnesyldiphosphate synthase. Activated cells are potent for killing a broad range of tumor cells and demonstrated the capacity for tumor reduction in murine xenotransplant tumor models. Translating these findings to the clinic produced prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
103
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 117 publications
(124 reference statements)
0
103
0
Order By: Relevance
“…Recent study showed gamma delta T cells produce interleukin‐17A that promotes bone formation and facilitates bone fracture healing . As gamma delta T cells have extraordinary properties including the capacity for tumor cell killing, the activated gamma delta T cells during fractured bone healing may have killed both mononuclear cells and multinucleated osteoclast‐type giant cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study showed gamma delta T cells produce interleukin‐17A that promotes bone formation and facilitates bone fracture healing . As gamma delta T cells have extraordinary properties including the capacity for tumor cell killing, the activated gamma delta T cells during fractured bone healing may have killed both mononuclear cells and multinucleated osteoclast‐type giant cells.…”
Section: Discussionmentioning
confidence: 99%
“…43 Recent study showed gamma delta T cells produce interleukin-17A that promotes bone formation and facilitates bone fracture healing. 44 As gamma delta T cells have extraordinary properties including the capacity for tumor cell killing, 45 et al reported that the rate for major complications was higher after resection when compared with curettage with adjuvants (16% versus 4%, respectively). 29 In contrast, in the present study, the complications rate was comparable between curettage and resection (15.2% versus 15.4%).…”
Section: Discussionmentioning
confidence: 99%
“…124,125 An additional perquisite of using cd T cells for immunotherapy lies in their ability to crosspresent processed tumor antigen to ab T cells, and this process is retained in CAR-cd T cells, further enhancing their antitumor effects. 124,125 An additional perquisite of using cd T cells for immunotherapy lies in their ability to crosspresent processed tumor antigen to ab T cells, and this process is retained in CAR-cd T cells, further enhancing their antitumor effects.…”
Section: Applications Of CD T Cells In Immunotherapymentioning
confidence: 99%
“…Recently, cd T cells have been incorporated into CAR therapy, producing sufficient cells from Vd1 + and Vd2 + subsets for clinical studies. 124,125 An additional perquisite of using cd T cells for immunotherapy lies in their ability to crosspresent processed tumor antigen to ab T cells, and this process is retained in CAR-cd T cells, further enhancing their antitumor effects. 124…”
Section: Applications Of CD T Cells In Immunotherapymentioning
confidence: 99%
“…Proliferation of PC tumor cells was suppressed in severely immunodeficient mice, and an initial study using the gd T-cell agonist zoledronate in combination with IL-2 presented with promising results in patients with metastatic PC. 37 Immune responses against the tumors are dependent on the subset of T cell recruited to the site of the tumor, which is dependent on the chemokine and cytokine gradient defining the specific type of inflamed cells. The Tregs, through their immunosuppressive effects, favor tumorpromoting characteristics; and the same has been demonstrated in PC patients, in whom elevated levels of Tregs conferred poor survival rates and a greater possibility of death.…”
Section: T Lymphocytesmentioning
confidence: 99%